Analysis of Village Government Policy and Human Resource Quality - Luturmas, Yulius (Yayasan Gema Bina Nusantara, 2024)
Human resource development within the scope of village government is a problem that is always faced in efforts to educate the nation's life according to the mandate of the 1945 Constitution. In this regard, this study aims to determine the mechanism for determining village government policy in accommodating community needs related to human resource development for the Ilngei Village community. The research data obtained indicates that the mechanism for formulating the Ilngei Village Government Policy has not been carried out properly. This affects the low quality of human resources owned by the Ilngei Village community.